Rare taxa have potential to make metabolic contributions in enhanced biological phosphorus removal ecosystems - Christopher E. Lawson; Blake J. Strachan; Niels W. Hanson; Aria S. Hahn; Eric R. Hall; Barry Rabinowitz; Donald S. Mavinic; William D. Ramey; Steven J. Hallam (Environmental Microbiology, 2015)
Summary Enhanced biological phosphorus removal ( EBPR ) relies on diverse but specialized microbial communities to mediate the cycling and ultimate removal of phosphorus from municipal wastewaters. However, little is known about microbial activity and dynamics in relation to process fluctuations in EBPR ecosystems. Here, we monitored temporal changes in microbial community structure and potential activity across each bioreactor zone in a pilot‐scale EBPR treatment plant by examining the ratio of small subunit ribosomal RNA ( SSU r RNA ) to SSU r RNA gene (r DNA ) over a 120 day study period. Although the majority of operational taxonomic units ( OTUs ) in the EBPR ecosystem were rare, many maintained high potential activities based on SSU r RNA : r DNA ratios, suggesting that rare OTUs contribute substantially to protein synthesis potential in EBPR ecosystems. Few significant differences in OTU abundance and activity were observed between bioreactor redox zones, although differences in temporal activity were observed among phylogenetically cohesive OTUs . Moreover, observed temporal activity patterns could not be explained by measured process parameters, suggesting that other ecological drivers, such as grazing or viral lysis, modulated community interactions. Taken together, these results point towards complex interactions selected for within the EBPR ecosystem and highlight a previously unrecognized functional potential among low abundance microorganisms in engineered ecosystems.